2021
DOI: 10.1177/20471734211036462
|View full text |Cite
|
Sign up to set email alerts
|

Development of economic competence of students at general grammar schools through a non-formal opportunity to learn with experts

Abstract: For many years empirical studies have repeatedly pointed to the need to improve the economic competence of adolescent and young adults. This demand is already reflected – at least in part – in the inclusion of economic content in the curriculum of general educational schools. However, the curricular implementation seems to be only partially comprehensive enough to sufficiently support the acquisition of economic competence, so that non-formal and informal learning opportunities do not lose their importance as … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 50 publications
(68 reference statements)
0
2
0
Order By: Relevance
“…Schmidt et al (2015) study on PISA 2012 data showed that OTL measures were significantly related to students' mathematics performance. Siegfried and Wuttke (2021) recently found that OTL also had a positive effect on the financial literacy of young people, but the effect had a clear gender difference. According to their study, OTL significantly affected only young females' financial literacy (Siegfried & Wuttke, 2021).…”
Section: Financial Socialization Factors Financial Confidence and Fin...mentioning
confidence: 99%
See 1 more Smart Citation
“…Schmidt et al (2015) study on PISA 2012 data showed that OTL measures were significantly related to students' mathematics performance. Siegfried and Wuttke (2021) recently found that OTL also had a positive effect on the financial literacy of young people, but the effect had a clear gender difference. According to their study, OTL significantly affected only young females' financial literacy (Siegfried & Wuttke, 2021).…”
Section: Financial Socialization Factors Financial Confidence and Fin...mentioning
confidence: 99%
“…Siegfried and Wuttke (2021) recently found that OTL also had a positive effect on the financial literacy of young people, but the effect had a clear gender difference. According to their study, OTL significantly affected only young females' financial literacy (Siegfried & Wuttke, 2021). The OTL approach aims to examine how learning opportunities in financial education have been available for students through their school education (Schmidt et al, 2014).…”
Section: Introductionmentioning
confidence: 99%